JUSTIFICATION FOR RE-LOOK CYSTOSCOPY AFTER POSTERIOR URETHRAL VALVE FULGURATION - Nawaz, Gul; Hussain, Ijaz; Muhammad, Shujah; Jamil, Muhammad Imran; Rehman, Asad Ur; Iqbal, Nadeem; Akhter, Saeed (Journal of Ayub Medical College Abbottabad, 2017)
Background: Posterior urethral valve (PUV) is life-threatening congenital anomaly of the urinary tract that results in vesicoureteric reflux, recurrent UTI, voiding dysfunction and renal insufficiency if not treat timely. Endoscopic ablation of posterior urethral valves using cold knife or laser is the current gold standard therapy. Many urologists go for repeat cystoscopy to see residual valve or stricture while others repeat VCUG to measure the posterior to anterior urethral ratio for residual obstruction. In this study, we have standardized by regularly doing re-look cystoscopy at 3 months whether the child is symptomatic or not to see justification for re-look cystoscopy after PUV ablation. Methods: In this prospective study, first 50 cases that underwent posterior urethral valve fulguration were included. Diagnosis of posterior urethral valve was made by voiding symptoms, ultrasonography and confirmed by voiding cysto-urethrogram (VCUG). All children were treated by endoscopic fulguration of posterior urethral valves (PUV) using cold knife as urethral valvotome and were followed clinically for voiding symptoms and with ultrasonography and laboratory test at 3 and 6 months. All patients underwent re-look cystoscopy at three months to see residual valves irrespective of their clinical improvement. Results: Mean age at presentation was 4.9±3.2 years. The most common symptoms were poor stream (76%), straining at voiding (72%), dribbling of urine (54%), fever (42%) and urinary retention (14%). Residual valves on re-look cystoscopy were seen in 78%. Four (8%) patients had urethral stricture on re- look cystoscopy. Conclusion: We suggest routine re-look cystoscopy after primary fulguration of PUV to pick more residual obstructive valves. Keywords: PUV; Endoscopic fulguration; Residual valve